The Role of Teacher Leaders in Developing Effective Learning Ecosystems: A Case Study of Elementary Schools in Indonesia - Sari, Indry Novita; Faiz, Aiman; Afendi, Arief Hidayat (Papanda Publisher, 2025)
This study examined the role of Teacher Leaders (Guru Penggerak) in developing effective learning ecosystems at SDN 1 Sumber, Cirebon Regency, Indonesia. The research employed a qualitative case study design to explore how Teacher Leaders implement the Merdeka Curriculum and create collaborative learning environments. Data were collected through systematic observations over two months, semi-structured interviews with four Teacher Leaders, two non-teacher leader educators, one principal, and six students, alongside document analysis of lesson modules and assessment reports. Thematic analysis revealed that Teacher Leaders functioned as catalysts in transforming traditional pedagogical approaches through student-centered lesson planning, integration of Pancasila Student Profile values, and implementation of innovative strategies including project-based learning (35% of observed activities), differentiated instruction (28%), and flipped classroom approaches (20%). Teacher Leaders successfully fostered collaborative partnerships among teachers, students, parents, and community members, reflecting Ki Hadjar Dewantara's Tri Pusat Pendidikan concept. Principal support through policy frameworks, professional development opportunities, and technology procurement strengthened Teacher Leader effectiveness. However, implementation faced significant challenges including infrastructure limitations, digital literacy gaps among senior teachers, and resistance to pedagogical change. Despite these barriers, Teacher Leaders demonstrated creativity in overcoming constraints through alternative strategies and resource optimization. The study contributes empirical evidence of teacher leadership effectiveness in resource-limited Indonesian elementary contexts while validating international distributed leadership theories within Southeast Asian educational settings. Findings suggest that systematic Teacher Leader program expansion, targeted infrastructure support, and institutional collaboration frameworks are essential for sustainable educational transformation. Future research should examine multi-site implementations and long-term impacts on student achievement outcomes.